Analysis of Employee Work Motivation at BMT Ta'awun Sumedang - Febriansyah, R. Mohamad Esa Febriansyah1; Nurfauzia, Fadila; Anggini, Megah Dewi (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2025)
An organization will develop and progress in accordance with the vision and mission that has been planned by the organization. These human resources are employees who have a commitment to be able to motivate themselves to be better according to what is exp ected. BMT Ta'awun has not been optimal in its implementation because the provision of existing work facilities and facilities is not adequate, job training has not supported the improvement of employee skills and compensation has not been optimal because salaries are not in accordance with the UMR. BMT Ta'awun Sumedang implements a structured approach, one of which is by implementing a balanced reward and sanction system. This research was conducted at the BMT Ta'awun Sumedang In the research that the auth or conducted using qualitative methods. Data collection techniques used interview and observation techniques. The informants in this study were around 6 people consisting of leaders, heads of finance and operations, heads of marketing and financing, and subordinates. The results of the study Social needs at BMT Ta'awun Sumedang are good with not only work attachment but more to family attachment. The need for self-esteem and recognition at BMT Ta'awun Sumedang has been implemented with rewards, in the form of incentives and job promotions. As well as the need for self-actualization at BMT Ta'awun Sumedang is good, with appropriate performance assessments and with employees being included in training, freedom of speech, so that employees can develop